2021
DOI: 10.3390/cancers13112791
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Prognosis Prediction of Pancreatic Ductal Adenocarcinoma Using Integrated Clinico-Genomic Data of Endoscopic Ultrasound-Guided Fine Needle Biopsy

Abstract: The aim of this study was to investigate the clinical utility of minimal specimens acquired from endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) and perform targeted deep sequencing as a prognosis prediction tool for pancreatic ductal adenocarcinoma (PDAC). A total of 116 specimens with pathologically confirmed PDAC via EUS-FNB were tested using CancerSCAN® panel for a customized targeted deep sequencing. Clinical prognostic factors significantly associated with survival in PDACs were as follows: sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…NF1 mutations were reported as potential biomarkers for poor prognosis in pancreatic ductal adenocarcinoma, 23 colorectal cancer. 24 In our study, 118 NF1 mutant patients and 236 NF1 wild‐type patients had enrolled for survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…NF1 mutations were reported as potential biomarkers for poor prognosis in pancreatic ductal adenocarcinoma, 23 colorectal cancer. 24 In our study, 118 NF1 mutant patients and 236 NF1 wild‐type patients had enrolled for survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…EUS-FNB data have been used to predict PDAC prognosis more accurately. Park et al (2021) obtained frequencies of gene mutations through targeted sequencing of EUS-FNB specimens from PDAC patients [107]. Their Cox regression model successfully classified patients into a high-risk group (median overall survival 5.95 months) and a low-risk group (median survival 15.27 months) based on genetic mutations detected from cyst fluid and clinical factors such as age, stage, and mass size.…”
Section: Survival Predictionmentioning
confidence: 99%
“…EUS-guided fine-needle aspiration (EUS-FNA) is the technique of choice for safely sampling the pancreas, with a pooled sensitivity and specificity for the diagnosis of PDAC of 85% and 98% respectively ( Hewitt et al, 2012 ). Beyond cytopathological evaluation, several studies have shown excellent performance of EUS-FNA samples from PDAC for DNA genomic analysis ( Larghi et al, 2020 ; Habib et al, 2021 ; Park et al, 2021 ). RNA analysis of EUS-acquired pancreatic samples is less extended than DNA based approaches, mainly because of the low yield and quality of RNA due to its easy degradation by pancreatic RNAases.…”
Section: Introductionmentioning
confidence: 99%